The Effect Of Concentration On Rice Ash Husk And Soaking On The Decrease HCN Galli (Lasio spinosa) Flour - Wahyu, Wahyu; Rahayuni, Tri; Purwayantie, Sulvi (Jurnal Sains Mahasiswa Pertanian, 2019)
Galli (Lasia spinosa) is one of uniqe rhizome from Sambas regency that never use and contain of HCN (cyanide acid). This acid was toxin in body and dose dependent could be death. For decreasing HCN has been done with rice ash husk and certain time. Â The goal of this research to obtain the effective of ash suspension and soaking time to decrease HCN of galli tuber. The research design used factorial of block design between rice husk ash concentration (10%, 20%, 30%) and time of (6, 12, 24 in hour). Data was analyzed by anova (Î± = 5%) and BNJ (Î± = 5%).The result showed that the higher of rice husk ash concentration and the long time of soaking, the lower of HCN content. The best treatment of galli powder obtain from rice husk ash concentration of 30% andÂ  soaking time for 24 hours with characteristic HCN content of 3.07 ppm, moisture content of 7,24%, ash of 5,49%, fat of 1,16 protein of 7,12%, crude fiber of 13,81% and carbohydrate of 81,47%.Key word : rice husk ash. soaking. HCN. flour. galli